A Comparative Study of Single and Dual Perfusion During End-ischemic Subnormothermic Liver Machine Preservation. Issue 11 (November 2018) - Brüggenwirth, Isabel M.A.; Moore, Carolina; Mahboub, Paria; Thijssen, Max F.; E, Xiaofei; Leuvenink, Henri G.D.; Mandrekar, Pranoti; Wang, Xiaofei; Kowalik, Timothy F.; Porte, Robert J.; Martins, Paulo N.
Abstract : Background: It remains controversial if arterial perfusion in addition to portal vein perfusion during machine preservation improves liver graft quality. Comparative studies using both techniques are lacking. We studied the impact of using single or dual machine perfusion of donation after circulatory death rat livers. In addition, we analyzed the effect of pulsatile versus continuous arterial flow. Methods: Donation after circulatory death rat livers (n = 18) were preserved by 6 hours cold storage, followed by 1 hour subnormothermic machine perfusion (20°C, pressure of 40/5 mm Hg) and 2 hours ex vivo warm reperfusion (37°C, pressure of 80/11 mm Hg, 9% whole blood). Machine preservation was either through single portal vein perfusion (SP), dual pulsatile (DPP), or dual continuous perfusion (DCP) of the portal vein and hepatic artery. Hydrodynamics, liver function tests, histopathology, and expression of endothelial specific genes were assessed during 2 hours warm reperfusion. Results: At the end of reperfusion, arterial flow in DPP livers tended to be higher compared to DCP and SP grafts. However, this difference was not significant nor was better flow associated with better outcome. No differences in bile production or alanine aminotransferase levels were observed. SP livers had significantly lower lactate compared to DCP, but not DPP livers. Levels of Caspase-3 and tumor necrosis factor-α were similar between the groups. Expression of endothelial genes Krüppel-like-factor 2 and endothelial nitric oxide synthase tended to be higher in dual perfused livers, but no histological evidence of better preservation of the biliary endothelium or vasculature of the hepatic artery was observed. Conclusions: This study shows comparable outcomes after using a dual or single perfusion approach during end-ischemic subnormothermic liver machine preservation.